PERENCANAAN LANSKAP BERBASIS MITIGASI BENCANA DI DESTINASI EKOWISATA PULAU SARONDE KABUPATEN GORONTALO UTARA - Rizkaf Zulfikar Kasim; Ute Lies Siti Khadijah; Cecep Ucu Rakhman; Rifki Rahmanda Putra (UHN IGB Sugriwa Denpasar, 2021)
Saronde Island Ecotourism Destinations are part of the Togean National Tourism Destination - Gorontalo and its surroundings as a New Ecotourism Destination in Indonesia. However, its vulnerability to an earthquake that may have the potential for a tsunami makes this ecotourism destination need to be supported by its ecological resilience against disasters that may directly impact the Saronde Island Ecotourism Destination. This study aims to analyze the potential for disasters and plan the arrangement of the landscape and vegetation in the Saronde Island Ecotourism Destination to reduce the risk if a disaster occurs in that destination. This research method uses a qualitative approach through several stages of planning processes. The informants in this study came from government circles in charge of tourism and disaster in North Gorontalo as well as from the management of the Saronde Island Ecotourism Destination. The results showed that Saronde Island is susceptible to earthquakes and tsunamis because it is on a fault line and has several historical records of earthquake source points in the northern part of the Sulawesi sea. So landscape planning through spatial planning and utilization of vegetation can be applied as an effort to bridge the ecological function of the island and the function of tourism, especially for the security and safety of tourists and local communities. Managers and local governments need to take firm structural measures, starting from determining island zoning, supporting facilities such as interpretation media, evacuation route and supporting non-structural regulations such as determining disaster mitigation scenarios.